Learning organisations in interdisciplinary environments - Jedvert, Frida; Persson, Viktor (My University, 2019)
Swedish universities play a key role making sure to encourage learning and knowledge transfer within their organisations. At Chalmers University of Technology so-called Areas of Advance have been developed which primarily aim to challenge major societal problems through multidisciplinary collaboration between different institutions and external actors. Previous research on the subject of interdisciplinary projects means it is good for promoting knowledge transfer (Jeong & Chi, 2007). Knowledge transfer is today becoming more and more a product and service in modern organisations. In order to be competitive, it is therefore necessary to work on maintaining knowledge and spreading it to the greatest possible extent (Jonsson, 2012). This study aims to identify the importance of the learning organisation characteristics and to what extent they are fulfilled by the Areas of Advance. Furthermore to describe a learning organisation with respect to the interdisciplinary environment and the Areas of Advance. The study is based on a quantitative survey and conducted qualitative interviews, literature review and document review. Results show that the top five learning organisation characteristics perceived as most important by the Areas of Advance were; External exchange, Holistic perspective, Leadership engagement, Openness, Transparency. The top five characteristics considered to be most fulfilled by the Areas of Advance were; Leadership engagement, Holistic perspective, External exchange, Openness, Flexibility. The description of a learning organisation with respect to interdisciplinarity and the Areas of Advance resulted in a list consisting of following characteristics; Flexibility, Transparency, Leadership engagement, Learning from mistakes, Reflection, Monitoring, Personal development.
Keywords: Learning; Learning Organisations; Interdisciplinary; Interdisciplinarity; Areas of Advance; Chalmers